Application of Fibre Bragg grating sensors for accurate deformation monitoring in civil structures: A literature review - Smailov, Nurzhigit; Tuleshov, Amandyk; Zhadiger, Torekhan; Issova, Аіnur; Zhanatayuly, Zhiger (International Journal of Innovative Research and Scientific Studies, 2025)
This research explores the deployment of Fiber Bragg Grating (FBG) fiber-optic sensors for embedded, high-precision deformation monitoring in civil infrastructure. The investigation emphasizes the potential of FBG sensors to be integrated into Structural Health Monitoring (SHM) systems and evaluates their performance under realistic experimental conditions. The study presents methods for embedding FBG sensors into concrete and steel structural elements, enabling continuous acquisition of strain, stress, and temperature variations in real time. Experimental analyses demonstrate that the sensors exhibit remarkable sensitivity, stability, and reliability, even when exposed to demanding environmental influences. Their consistent performance over extended periods highlights the robustness of FBG technology for long-term monitoring applications. Moreover, the findings confirm that early detection of structural irregularities is feasible, providing timely insights into emerging risks that could compromise integrity. By facilitating proactive maintenance strategies and enhancing safety assessments, FBG-based SHM systems significantly improve operational efficiency and extend the service life of critical infrastructure. These results underscore the suitability of FBG sensors as a key enabling technology for advancing modern monitoring practices in civil engineering.